2018
DOI: 10.1038/s41419-018-0801-9
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord-derived mesenchymal stem cells direct macrophage polarization to alleviate pancreatic islets dysfunction in type 2 diabetic mice

Abstract: Progressive pancreatic β-cell dysfunction is recognized as a fundamental pathology of type 2 diabetes (T2D). Recently, mesenchymal stem cells (MSCs) have been identified in protection of islets function in T2D individuals. However, the underlying mechanisms remain elusive. It is widely accepted that β-cell dysfunction is closely related to improper accumulation of macrophages in the islets, and a series of reports suggest that MSCs possess great immunomodulatory properties by which they could elicit macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 56 publications
2
63
0
Order By: Relevance
“…Taken together, these studies have demonstrated that the deficient autophagy in macrophages was correlated to systemic inflammation in type 1 and 2 diabetic mice. Additionally, several studies have shown that MSCs treatment elicited macrophages into M2 phenotype in type 2 diabetic models . In the present study, we confirmed that MSCs treatment improved mitochondrial bioenergetics, activated autophagy and elicited M2 Mφ polarization in DN mice, whereas the beneficial effect was blunted when autophagy was blocked with HCQ, indicating that immune‐regulation of MSCs is dependent on autophagy.…”
Section: Discussionsupporting
confidence: 85%
“…Taken together, these studies have demonstrated that the deficient autophagy in macrophages was correlated to systemic inflammation in type 1 and 2 diabetic mice. Additionally, several studies have shown that MSCs treatment elicited macrophages into M2 phenotype in type 2 diabetic models . In the present study, we confirmed that MSCs treatment improved mitochondrial bioenergetics, activated autophagy and elicited M2 Mφ polarization in DN mice, whereas the beneficial effect was blunted when autophagy was blocked with HCQ, indicating that immune‐regulation of MSCs is dependent on autophagy.…”
Section: Discussionsupporting
confidence: 85%
“…IL-1Ra can also regulate the phenotype switch of macrophages [49]. A previous study in T2DM mice has shown that MSCs infusion improved the b cell function through promoting the phenotype switch of macrophages in the diabetic mice islets [50]. Therefore it is possible that macrophages may also be involved in restoring the homeostasis of human T2DM islets.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were then randomly assigned into two groups ( n = 8 per group), type 2 diabetes (T2D) and negative control group. The mice in T2D group were generated by a combination administration of streptozotocin (STZ) and a high‐fat diet (HFD) according to the previous reports . After 4 h fasting, T2D group mice received an intraperitoneal injection of STZ (Sigma‐Aldrich, St Louis, MO, USA) in citrate buffer (120 mg/kg body weight).…”
Section: Methodsmentioning
confidence: 99%
“…The mice in T2D group were generated by a combination administration of streptozotocin (STZ) and a highfat diet (HFD) according to the previous reports. [21,22] After 4 h fasting, T2D group mice received an intraperitoneal injection of STZ (Sigma-Aldrich, St Louis, MO, USA) in citrate buffer (120 mg/kg body weight). After 3 weeks of STZ injection, T2D group mice were given HFD (21.8 kJ/g) for 7 weeks.…”
Section: Experimental Animals and Groupsmentioning
confidence: 99%